Menguji Kedahsyatan Dimensi Foodstagram dalam Memikat Konsumen Membeli Ulang di Tahoma Coffee and Eatery - Indira, Indira Chintya Nik Arsana Putri; Darma, Gede Sri (Universitas Hamzanwadi, 2024)
In the current competitive business environment, understanding the factors that influence consumer repurchase intention is crucial for companies. Customer experience and product uniqueness are two of the key factors that can influence consumer repurchase intentions. This study aims to investigate the foodstagram dimension's ability to attract consumers to repurchase at Tahoma Coffee and Eatery. The number of samples involved in this study was 110, and the information was collected using a 10-point semantic scale questionnaire. The data analysis technique used is SEM-PLS. The results show that customer experience and product uniqueness have a positive and significant effect on repurchase intention. The customer experience has a positive and significant effect on brand preference. The foodstagram dimension reflected using visibility has not been proven to moderate the relationship between the customer experience variable, the product uniqueness variable, and the repurchase intention variable. However, the foodstagram dimension reflected by attractiveness can positively moderate the relationship between the customer experience variable and the product uniqueness variable with the repurchase intention variable. It is concluded that the attractiveness dimension of the foodstagram is a variable that strengthens the relationship between customer experience and product uniqueness with repurchase intention.